PROBLEMS AND DIFFICULTIES OF SPEAKING AT MUHAMMADIYAH LAMPUNG UNIVERSITY STUDENTS IN COVID PANDEMIC - Dyah Sih Pratiwi; Candraning Prihatini (Program Studi Tadris Bahasa Inggri Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2021)
The purpose of this research was to describe the problem and difficulties of speaking at Muhammadiyah Lampung University students in Covid pandemic. This research used descriptive qualitative research. The subject of this research were Muhammadiyah Lampung University students at first semester in English Education Department. The data collecting technique of this research used questionnaire. The result of this research indicated that the students in first semester of English Department have some problems and difficulties in speaking subject during Covid pandemic. There some problems and difficulties in practicing speaking in Covid pandemic namely 1) understanding the conversation; (2) less of vocabularies; (3) pronunciation; (4) shy, (5) Worrying for making grammatical errors, (6) lack of Technology, and (7) lack of motivation. Based on the analysis of questionnaire indicated that that 5 % in meaning, 22 % in vocabularies, 8 % in pronunciation, 32 % in shy, 8% Worrying for making grammatical errors, 10% lack of Technology, and 15% lack of motivation. Based on the data the majority students indicated that confidence is the most problem in speaking skill.